Mathematical Model of Amplified Stimulated Raman Scattering and Fiber Raman Amplifier - Kbashi, Hani J. (Iraqi Journal of Physics, 2008)
The result of a developed mathematical model for predicting the designparameters of the fiber Raman amplifier (FRA) are demonstrated. The amplificationparameters are tested at different pump power with different fiber length. Recently,the FRA employed in optical communication system to increase the repeater distanceas will as the capacity of the communication systems. The output results show, thathigh Raman gain can be achieved by high pumping power, long effective area thatneed to be small for high Raman gain. High-stimulated Raman gain coefficient isrecommended for high Raman amplifier gain, the low attenuation of the pump and thetransmitted signal in the fiber lead to high Raman gain.